2019
DOI: 10.4025/actascitechnol.v41i2.35043
|View full text |Cite
|
Sign up to set email alerts
|

Content of phenolic compounds in fruit processing residues by mass spectrometry

Abstract: This study identified and quantified five phenolic compounds, and evaluated the antioxidant capacity in vitro of fifteen native and exotic Brazilian fruit seeds that are typically discarded as waste. The contents of phenolic compounds were determined by ultra-performance liquid chromatography coupled with tandem mass spectrometry, and the antioxidant capacity was determined by oxygen radical absorbance capacity (ORAC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH•) antioxidant assays. The results showed the antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In the study developed by Lescano et al (2023) were quantified 27.3 ± 0.1 mg mL -1 of quinic acid, 132.3 ± 0.7 of mg mL -1 of rutin, 26.9 ± 0.2 mg mL -1 of apigenin 6,8-diglucoside and 14.1 ± 0.1 mg mL -1 of (luteolin 8-C-glucoside. Vagula et al, (2019) quantified 393.005 μg g -1 of gallic acid and 0.847 μg g -1 of myricetin in the pulp of C. guazumifolia, with chlorogenic, vanillic acid and being below the quantification limit (Figure 8).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…In the study developed by Lescano et al (2023) were quantified 27.3 ± 0.1 mg mL -1 of quinic acid, 132.3 ± 0.7 of mg mL -1 of rutin, 26.9 ± 0.2 mg mL -1 of apigenin 6,8-diglucoside and 14.1 ± 0.1 mg mL -1 of (luteolin 8-C-glucoside. Vagula et al, (2019) quantified 393.005 μg g -1 of gallic acid and 0.847 μg g -1 of myricetin in the pulp of C. guazumifolia, with chlorogenic, vanillic acid and being below the quantification limit (Figure 8).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Different extracts of A. atemoya and the phytochemical constituents isolated from several parts of the plant exhibit pharmacological activities such as anti-inflammatory and antinociceptive activity [45], antioxidant [11,31,46,47], antibacterial [46], anti-angiogenic [12], neuroprotective and anti-Alzheimer's [9,11], anticancer [20,31,44], hypolipidemic [48] and antiobesity activity [49], in both in vivo and in vitro studies (Table 1).…”
Section: Pharmacological Properties Of a Atemoyamentioning
confidence: 99%
“…In an in vitro study, the methanolic seed extract of A. atemoya was examined for antioxidant potential [47]. Both 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and oxygen radical absorbance capacity (ORAC) assays were employed.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…9 Some studies published in the literature show that Passiflora edulis seeds are also rich in bioactive compounds that present high antioxidant capacity 7 and anti-inflammatory, vasorelaxing, 4,[10][11][12] antitumor, antidiabetic and anti-adipogenic properties. [13][14][15] Vagula et al 16 identified phenolic compounds in Passiflora edulis seeds such as gallic acid (hydroxybenzoic acid) and chlorogenic acid (hydroxybenzoic acid).…”
Section: Introductionmentioning
confidence: 99%